Are nutrition messages lost in transmission? Assessing the quality and consistency of diabetes guideline recommendations on the delivery of nutrition therapy. Issue 12 (December 2016) - Hale, Kelli; Capra, Sandra; Bauer, Judy
Highlights: This study assessed the quality of Clinical Practice Guidelines for Diabetes. Recommendations on the delivery of nutrition therapy were categorised. A wide range of patient and practitioner focused topics were identified. Broad guidelines were of higher quality than nutrition specific ones. Nutrition-specific guidelines need to be more patient-focused. Abstract: Aim: To provide an overview of (1) the consistency of Type 2 Diabetes Clinical Practice Guidelines recommendations on the delivery of nutrition therapy and (2) Clinical Practice Guideline quality. Methods: Large international clinical practice guideline repositories, diabetes organisation websites, and electronic databases (Pubmed, Scopus), were searched to identify Clinical Practice Guidelines for adults with type 2 diabetes published 2005 to August 2014. Recommendations on the delivery of nutrition therapy were extracted and inductive content analysis was used to analyse consistency. Two researchers independently assessed guideline quality using the AGREE II tool. Results: Nine topics were identified from the recommendations. Overall the consistency of the recommendations was related to guideline type. Compared with nutrition-specific guidelines, the broad ones had a broader focus and included more patient-focused recommendations. The ten Clinical Practice Guidelines assessed included six broad guidelines and four nutrition specific guidelines. Based on AGREE II analysis, the broad guidelines were higher quality than nutrition-specific ones. Conclusions: Broad Clinical Practice Guidelines were higher quality and included more patient-focused recommendations than nutrition-specific ones. Practice implications: Our findings suggest a need for nutrition-specific guidelines to be modified to include greater patient-focus, or for practitioners delivering nutrition therapy to adopt broad Clinical Practice Guidelines.